7.4k views
3 votes
Which is equivalent to the expression? 4(x + 5) + 4x + 8 A) 4(2x + 7) B) 5x + 17 C) 8(x + 4) D) 8x + 13

User Mglmnc
by
4.8k points

2 Answers

2 votes

Answer:

The correct option is A) 4(2x + 7).

Explanation:

Consider the provided expression.

4(x + 5) + 4x + 8

Apply the distributive property:
a(b+c)=ab+ac

4(x + 5) + 4x + 8 = 4x + 20 + 4x + 8

Now add the like terms.

8x + 28

The above expression can be written as:

4 × 2x + 4 × 7

4(2x + 7)

Hence, the correct option is A) 4(2x + 7).

User Rharishan
by
4.5k points
0 votes

Answer:

A) 4(2x + 7) is your answer.

Explanation:

Distribute 4 to all terms within the first parenthesis.

4(x + 5) = 4x + 20

4x + 20 + 4x + 8

Simplify. Combine like terms.

4x + 4x + 20 + 8

8x + 28

A) 4(2x + 7) is your answer.

Simplify. Distribute 4 to all terms within the parenthesis

4(2x) = 8x

4(7) = 28

8x + 28 = 8x + 28 ∴ 4(x + 5) + 4x + 8 = 4(2x + 7)

~

User Andrei Astrouski
by
4.9k points